Cell genesis and dendritic plasticity: a neuroplastic pas de deux in the onset and remission from depression - Pinheiro, António Mateus (2013)
Brain neuroplasticity is increasingly considered to be an important component of both the pathology and treatment of depressive spectrum disorders. Recent studies shed light on the relevance of hippocampal cell genesis and cortico-limbic dendritic plasticity for the development and remission from depressive-like behavior. However, the neurobiological significance of neuroplastic phenomena in this context is still controversial. Here we summarize recent developments in this topic and propose an integrative interpretation of data gathered so far.